Identification and modulation of a voltage-dependent anion channel in the plasma membrane of guard cells by high-affinity ligands. - Marten, I (1992)
Guard cell anion channels (GCAC1) catalyze the release of anions across the plasma membrane during regulated volume decrease and also seem to be involved in the targeting of the plant growth hormones auxins. We have analyzed the modulation and inhibition of these voltage-dependent anion channels by different anion channel blockers. Ethacrynic acid, a structural correlate of an auxin, caused a shift in activation potential and simultaneously a transient increase in the peak current amplitude, whereas other blockers shifted and blocked the voltage-dependent activity of the channel. Comparison of dose-response curves for shift and block imposed by the inhibitor, indicate two different sites within the channel which interact with the ligand. The capability to inhibit GCAC1 increases in a dose-dependent manner in the sequence: probenecid less than A-9-C less than ethacrynic acid less than niflumic acid less than IAA-94 less than NPPB. All inhibitors reversibly blocked the anion channel from the extracellular side. Channel block on the level of single anion channels is characterized by a reduction of long open transitions into flickering bursts, indicating an interaction with the open mouth of the channel. IAA-23, a structural analog of IAA-94, was used to enrich ligand-binding polypeptides from the plasma membrane of guard cells by IAA-23 affinity chromatography. From this protein fraction a 60 kDa polypeptide crossreacted specifically with polyclonal antibodies raised against anion channels isolated from kidney membranes. In contrast to guard cells, mesophyll plasma membranes were deficient in voltage-dependent anion channels and lacked crossreactivity with the antibody.